Accounting information systems - Gelinas, Ulric J. (South-Western College, 1999)
Introduction to accounting information systems. Intelligent systems for aiding decision making. Documenting information systems. Data management and electronic commerce: Database management systems, rrelational databases and SQL, electronic commerce. Internal control: controlling information systems: a control framework, controlling information systems: IT processes, controlling information systems: technology-related application controls. AIS applications: the order entry/sales (OE/S) system, the billing/accounts receivable/cash receipts system...